Principles of bloodstain pattern analysis : theory and practice - James, Stuart H.; Kish, Paul Erwin; Sutton, T. Paulette (Boca Raton, FL : CRC, 2005)
Principles of Bloodstain Pattern Analysis: Theory and Practice presents an in-depth investigation of this important subject matter. A multidisciplinary approach is presented throughout the book that uses scene and laboratory examinations in conjunction with forensic pathology, forensic serology, and chemical enhancement techniques. Emphasis is on a thought process based on taxonomic classification of bloodstains that takes into account their physical characteristics of size, shape, and distribution, and the specific mechanisms that produce them. Individual chapters analyze case studies, with two chapters specifically discussing the details of legal issues as they pertain to bloodstain pattern analysis. Information highlighted throughout the book includes an examination of bloodstained clothing and footwear, the essentials of bloodstain photography, and information on bloodstain pattern analysis for crime scene reconstruction. Dramatic color images of bloodletting injuries, bloodstains, and crime scenes are also presented to compliment the technical content of this resource.--BOOK JACKET
Front Cover -- Foreword -- Preface -- The Authors -- Contributors -- Acknowledgments -- Contents -- Chapter 1: Introduction to Bloodstain Pattern Analysis -- Chapter 2: Medical and Anatomical Aspects of Bloodshed -- Chapter 3: Biological and Physical Properties of Human Blood -- Chapter 4: Physical Properties of Bloodstain Formation -- Chapter 5: Passive Bloodstains -- Chapter 6: Formation of Spatter and Spatter Associated with a Secondary Mechanism -- Chapter 7: Impact Spatter Mechanisms -- Chapter 8: Spatter Associated with a Projection Mechanism -- Chapter 9: Altered Bloodstain Patterns -- Chapter 10: Determination of the Area of Convergence and Area of Origin of Bloodstain Patterns -- Chapter 11: Directional Analysis of Bloodstain Patterns with a Computer -- Chapter 12: Documentation and Examination of Bloodstain Evidence -- Chapter 13: Evaluation of Bloodstain Patterns at the Scene -- Chapter 14: Presumptive Testing and Species Determination of Blood and Bloodstains -- Chapter 15: The Detection of Blood Using Luminol -- Chapter 16: Chemical Enhancement of Latent Bloodstain Impressions -- Chapter 17: Approaching the Bloodstain Pattern Case -- Chapter 18: Report Writing Chapter -- 19: Legal and Ethical Aspects of Bloodstain Pattern Evidence -- Chapter 20: Bloodstain Pattern Analysis: Postconviction and Appellate Application -- References -- Appendix A: Trigonometric Tables-Sine and Tangent Functions -- Appendix B: Metric Measurements and Equivalents -- Appendix C: Scene and Laboratory Checklists -- Appendix D: Biohazard Safety Precautions -- Appendix E: Court Decisions Relating to Bloodstain Pattern Analysis -- Appendix F: Court Decisions Relating to Presumptive Blood Tests -- Glossary of Terminology - Index.
Includes bibliographical references (p. 497-504) and index.
Keywords: Blood Stains; Crime; Wounds and Injuries